2014
DOI: 10.1128/jvi.02361-13
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sequence Coverage through Combined Targeting of Variant and Conserved Epitopes Correlates with Control of HIV Replication

Abstract: A major challenge in the development of an HIV vaccine is that of contending with the extensive sequence variability found in circulating viruses. Induction of HIV-specific T-cell responses targeting conserved regions and induction of HIV-specific T-cell responses recognizing a high number of epitope variants have both been proposed as strategies to overcome this challenge. We addressed the ability of cytotoxic T lymphocytes from 30 untreated HIV-infected subjects with and without control of virus replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 68 publications
4
17
2
Order By: Relevance
“…The latter observation is further supported by our observation that individuals with higher viral load target more epitopes and at higher intensity (see Fig. S2 in the supplemental material), consistent with a model in which a higher viral load leads to a high cell surface viral peptide concentration that stimulates further responses (similar observations with respect to variant recognition within Gag have been reported previously [62]). Note that these results suggest but do not prove cause and effect, as the models we examined were by no means exhaustive.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The latter observation is further supported by our observation that individuals with higher viral load target more epitopes and at higher intensity (see Fig. S2 in the supplemental material), consistent with a model in which a higher viral load leads to a high cell surface viral peptide concentration that stimulates further responses (similar observations with respect to variant recognition within Gag have been reported previously [62]). Note that these results suggest but do not prove cause and effect, as the models we examined were by no means exhaustive.…”
Section: Resultssupporting
confidence: 77%
“…One explanation of the predictive ability of targeting beyond HLA alleles is that targeting is a cause of viral control. Another explanation is that increased virus load resulting from lack of control leads to the targeting of additional epitopes (62). To explore the relative likelihood of these two explanations, we considered how well alternative statistical models uniquely consistent with each explanation predicted the data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, escape processes during primary HIV infection have the potential to increase the breadth and depth of Gag-specific CTL responses. We recently reported that during chronic HIV infection, progressors maintain higher levels of epitope variant recognition than viremic controllers (36). Our current results demonstrate that cross-reactivity and induction of de novo responses to epitope variants over time may lead to the high levels of variant recognition observed during chronic progressive infection.…”
Section: Discussionmentioning
confidence: 54%
“…The IFN-␥/IL-2 FluoroSpot assay was used for detection of Gag-specific T-cell responses in all SPs and TPs as previously described (36). Briefly, cryopreserved peripheral blood mononuclear cells (PBMC) were thawed and incubated in R10 medium overnight before stimulation.…”
Section: Methodsmentioning
confidence: 99%